Ending fifty years of confusion: the anomalous record of the Pale-legged Warbler (Basileuterus signatus) in Colombia: El fin de cincuenta años de confusión: el registro anómalo de la reinita patipálida (Basileuterus signatus) en Colombia (Ornitología Colombiana, 2021)
I present evidence that the supposed Colombian record of the Pale-legged Warbler (Basileuterus signatus) is based upon a specimen of the Citrine Warbler (B. l. luteoviridis) that was incorrectly sexed and aged by the collector or preparator and identified in the absence of adequate comparative material. Examination and measurements of museum specimens of both species permitted definitive identification of the problematical specimen. I conclude that B. signatus should be removed from the list of the Colombian avifauna.